2015
DOI: 10.1007/s11948-015-9709-2
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Clinical Ethics Consultation in German Hospitals

Abstract: In order to build on the information that was obtained in the course of the first study, a follow-up survey was conducted first by phone and subsequently in a written form between August and October 2014. We contacted 1.858 hospitals in all of Germany for the follow-up survey by phone. In cases where a hospital had not participated in the first study, the willingness to participate in the follow-up survey was established in advance. The survey's dispatch was ensured in the case of acceptance. The same structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 5 publications
0
15
0
4
Order By: Relevance
“…Although we obtained a broad range of information on CES in German forensic psychiatric institutions, our study has several limitations. First, although the overall response rate of 36% corresponds with those of comparable studies (7), it cannot be considered as being representative. Ethics might not play a significant role in non-responding hospitals; consequently, they would not participate in a survey assessing ethics support.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Although we obtained a broad range of information on CES in German forensic psychiatric institutions, our study has several limitations. First, although the overall response rate of 36% corresponds with those of comparable studies (7), it cannot be considered as being representative. Ethics might not play a significant role in non-responding hospitals; consequently, they would not participate in a survey assessing ethics support.…”
Section: Discussionmentioning
confidence: 83%
“…Special curricula have been developed to train clinical ethics consultants in the required competences [see, for example, (6)]. In Germany, the number of hospitals offering clinical ethics consultation has steadily increased in the last two decades (7). In psychiatry, however, structured ethics consultation has developed at a slower rate than in other medical disciplines, but it is considered to be relevant and helpful for moral case deliberation and an unprejudiced decision-making process (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…B. klinische oder ambulante Ethikkomitees) sowie konkrete Beratungsangebote (wie z. B. moderierte Fallbesprechungen), wie sie inzwischen in jedem zweiten Krankenhaus [20] sowie vereinzelt auch in Pflegeeinrichtungen und im ambulanten Bereich [21] angeboten werden, zielen darauf, besonders in Dissenssituationen den Entscheidungsprozess zu moderieren und zu erleichtern und eine Kultur der strukturierten Entscheidungsfindung zu fördern [4,22,23].…”
Section: Merke Das U U Kulturell Unterschiedliche Verständnis Derunclassified
“…Germany The establishment of a HEC is mandatory in all hospitals registered in the Christian Association of Hospitals in Germany (22). According to a new study in Germany, the percentage of hospitals with HECs was found to be 86.4% (45). Croatia Among European countries, Croatia achieved the legal requirements for the establishment of ethics committees around 1997.…”
Section: United Kingdommentioning
confidence: 99%